Plan estratégico para el mejoramiento de la calidad del servicio de prestación externa (Iess) dela clínica odontológica occidental del cantón La Maná periodo 2014-2016 - Flores Zamora, Vanessa Angélica (2015)
The current thesis project was implemented in the West Dental Clinic located on Avenue May 19, Cantón La Maná, Cotopaxi province; with the general goal to design a strategic plan for improving the quality of service delivery External (IESS) of Western dental clinic Cantón La Maná period 2014-2016; by implementing inductive and analytical methods that allowed analyzing the data obtained through surveys of service users external provision (IEES); likewise the external and internal analysis of the current situation of the clinic was performed using SWOT knowing the strengths of the clinic is to have a good infrastructure and experienced staff in the same way it was established that there are disturbing weaknesses as absence of the mission, vision a flowchart of functions and manual users. Therefore we proceeded to design a proposed strategic direction for clinical focus efforts enabling towards specific objectives in the future; complemented by a training plan and a manual care users, same that are focused to improve the quality of external service provision (IESS) for which it is recommended to socialize and implement the suggestions made.